Ultrasound-induced cavitation renders prostate cancer cells susceptible to hyperthermia: Analysis of potential cellular and molecular mechanisms - Hu, Shaonan; Zhang, Xinrui; Melzer, Andreas; Landgraf, Lisa (Frontiers in Genetics, 2023)
Focused ultrasound (FUS) has become an important non-invasive therapy for prostate tumor ablation via thermal effects in the clinic. The cavitation effect induced by FUS is applied for histotripsy, support drug delivery and the induction of blood vessel destruction for cancer therapy. Numerous studies reported that cavitation-induced sonoporation could provoke multiple anti-proliferative effects on cancer cells. Therefore, the combination of FUS-induced cavitation and thermal treatment is of great interest but research in this field is inadequate. In our study, monolayer prostate cancer cells (LNCap and PC-3) were first exposed to 40s FUS-induced cavitation using a special high-throughput FUS system with a customized 1.467 MHz single-focused transducer, followed by water bath hyperthermia (HT). The effects of FUS-induced cavitation to standard hyperthermia (HT) were investigated comprehensively at the cellular and molecular level in human prostate cancer in vitro. Short-term and long-term additive effects of FUS (short FUS with cavitation) to HT at the cellular level are reducing cell invasion, metabolic activity and clonogenic survival. FUS-induced cavitation may increase the effects of HT by interrupting cell membranes, inducing the DNA double-strand breaks and cell cycle arrest and blocking the androgen receptor signal pathway of the prostate cancer cells, with the potential to be a promising adjuvant therapy in prostate cancer treatment.